Combining Odontochronology, Tooth Wear Assessment, and Linear Enamel Hypoplasia (LEH) Recording to Assess Pig Domestication in Neolithic Henan, China. (4th February 2014) - Pike‐Tay, A.; Ma, X.; Hou, Y.; Liang, F.; Lin, M.; Peterson, V.
Abstract: Mandibles of Sus scrofa (wild boar/pig) from ritual pits H160 and H208 of Longshangang, a Late Yangshao Neolithic site in Xichuan County, Henan, were analyzed for evidence of domestication. Three methods of dental analysis were applied: odontochronology, tooth wear assessment, and linear enamel hypoplasia (LEH) recording, which provide age at death, season of kill, and season of birth data. We investigate whether: (i) the LEH height frequencies on the second molars of the mandibles correspond with the possibility of double farrowing and (2) double farrowing is supported by the season of and age at slaughter data. If so, these data suggest a substantial degree of human management of suids at the site. Copyright © 2014 John Wiley & Sons, Ltd.